Direction‐Sensitive Magnetophotonic Surface Crystals. Issue 10 (16th August 2021) - Rowan-Robinson, Richard M.; Hurst, Jérome; Ciuciulkaite, Agne; Chioar, Ioan-Augustin; Pohlit, Merlin; Zapata-Herrera, Mario; Vavassori, Paolo; Dmitriev, Alexandre; Oppeneer, Peter M.; Kapaklis, Vassilios
Abstract : Nanometer‐thin rare‐earth–transition‐metal (RE–TM) alloys with precisely controlled compositions and out‐of‐plane magnetic anisotropy are currently in the focus for ultrafast magnetophotonic applications. However, achieving lateral nanoscale dimensions, crucial for potential device downscaling, while maintaining designable optomagnetic functionality and out‐of‐plane magnetic anisotropy is extremely challenging. Herein, nanosized Tb18 Co82 ferrimagnetic alloys, having strong out‐of‐plane magnetic anisotropy, within a gold plasmonic nanoantenna array to design a micrometer‐scale magnetophotonic crystal that exhibits abrupt and narrow magneto‐optical (MO) spectral features that are both magnetic field and light incidence direction controlled are integrated. The narrow Fano‐type resonance arises through the interference of the individual nanoantenna's surface plasmons and a Rayleigh anomaly of the whole nanoantenna array, in both optical and MO spectra, which are demonstrated and explained using Maxwell theory simulations. This robust magnetophotonic crystal opens the way for conceptually new high‐resolution light incidence direction sensors, as well as for building blocks for plasmon‐assisted all‐optical magnetization switching in ferrimagnetic RE–TM alloys. Abstract : Microscale magnetophotonic surface crystals are revealed by building arrays of magnetoplasmonic nanoantennas with nanosized rare‐earth–transition‐metal ferrimagnetic TbCo alloys, displaying perpendicular magnetic anisotropy. Magneto‐optics is dramatically enhanced in such crystals via nanoantennas plasmons and their coupling into collective surface lattice modes. The result is a highly light direction‐sensitive optical surface with nanomagnetic functionality for the plasmon‐assisted all‐optical magnetization switching.